Prevalence of iron deficiency anemia and iron deficiency in a pediatric population with inflammatory bowel disease - Carvalho, FS (2017)
Iron deficiency is the most common cause of anemia in children with inflammatory bowel disease, although the real prevalence is unknown. Intravenous iron is suggested as the first line treatment. This study aims to determine the prevalence of iron deficiency anemia in children with inflammatory bowel disease followed in a Pediatric Gastroenterology Unit of a tertiary center and to evaluate this unit's experience with intravenous iron.